Human monoclonal anti-protective antigen antibody for the low-dose post-exposure prophylaxis and treatment of Anthrax - Qi Tang; Siping Xiong; Xudong Liang; Xingwang Kuai; Yiwen Wang; Changjun Wang; Zhenqing Feng; Jin Zhu (BMC Infectious Diseases, 2018)
Abstract Background Disease caused by Bacillus anthracis is often accompanied by high mortality primarily due to toxin-mediated injury. In the early disease course, anthrax toxins are secreted; thus, antibiotic use is limited to the early stage. In this regard, antibodies against the toxin component, protective antigen (PA), play an important role in protecting against anthrax. Therefore, we developed PA21, a fully human anti-PA immunoglobulin G monoclonal antibody. Methods Combining human Fab was screened from a phage library with human heavy constant regions. Enzyme-linked immune sorbent assay, Western blot analysis and immunoprecipitation test evaluated the binding ability of PA21. Moreover, the affinity and neutralizing activity of the antibody was detected in vitro while the protective effectiveness in 60 rats was also examined in vivo. Results The Fischer 344 rats challenged with the lethal toxin can be protected by PA21 at a concentration of 0.067 mg/kg. All six rats remained alive although PA21 was injected 24 h before the toxin challenge. PA21 did not influence the binding of PA to cell receptors and that of a lethal factor to PA. Conclusion The PA21 monoclonal antibody against PA can be used for emergency prophylaxis and anthrax treatment.